Diseño y desarrollo del sistema de gestión de la calidad para una industria extractora de aceite de palma africana - Espinoza Sau-Hing, Denisse (2010)
The costumers request products that satisfy their needs and expectations. Those needs and expectations are usually expressed like product’s specifications and they are usually called “costumer’s requirements”. The costumer’s requirement can be determined in the contracts by the client or the organization; however, the client is the person who always decides finally if the product is acceptable or not. Due the client’s expectations are changeable, the organizations must be improving their products and process continuously. The Quality Systems based in the international standard ISO 9001:2008 allow the organizations to analyze the costumer’s requirements, to carry out the requirements and expectations of the clients, to keep the process under control and to solve the quality’s problems. The objective of this work is to present the methods used to design and develop a quality system in a factory dedicated to the extraction and commercialization of palm oil including the politics, objectives, and process, developing of procedures, control’s formats, setting up quality indicators and cost/benefit analysis .